Analysis of the phytochemical profile of Terminalia chebula fruit extract with antioxidative and anti-inflammatory activity on breast cancer cell line - Sanakousar Patel; Sumangala Patil; Prachi P Parvatikar (Wolters Kluwer Medknow Publications, 2020)
Background: Occurrence of breast cancer is more among the female despite all the factors. Terminalia chebula is an important medicinal plant in Indian traditional medicine and it is the most frequently used herb in Ayurveda. The plant is described as an astringent, digestive, antiseptic, alterative, laxative, diuretic and carminative. Objective: To study the phytochemical analysis of Terminalia chebula fruit extract as well as to evaluate the synergistic activity of potent plant extracts as anti-oxidant and anti-inflammatory on the MCF-7 breast cancer cell line. Methodology: In the present study phytochemical constituent from selected plant material was extracted in different solvents. Antioxidant activity was evaluated by DPPH and FRAP assay against standard antioxidants. MTT assay was performed to find out the cytotoxic and anti-inflammatory effect on MCF- breast cancer cell line Result: Phytochemical analysis of the Terminalia chebula was performed which showed that alkaloids, phenols, flavonoids, and saponins. In the context of antioxidant assays almost selected extracts showed moderate activity but the ethanol extract of Terminalia chebula, proven to be having significant antioxidant activity overall extracts. The anti-inflammatory activity of the MCF-7 breast cancer cell line exhibited that good activity with IC50 value 228.82 μg/ml. Conclusion: The study showed that ethanolic extract fruit extract of Terminalia chebula have potential anticancer as well as anti-oxidant activity property.